El satanismo en la novela Allá lejos de Joris- Karl Huysmans - Carrillo Miani, Salvador (2025)
The present article analyzes Satanism in the novel Là-bas by Joris-Karl Huysmans, a representative author of the literary school of Decadence. In this work, Huysmans presents his paradoxical proposal of spiritualist naturalism, where he explores an interest in the experience of the mysterious and a departure from naturalism as conceived by Zola, who had been his mentor. For Là-bas, Huysmans conducted research on Satanism and occultism of his time, coming into contact with controversial figures associated with these movements. Satanism in the novel is embodied by two characters: the historical figure Gilles de Rais, known for his bloodthirsty and Satanic practices, and Docre, a Satanist who performs a black mass. This work served as a prelude to Huysmans’ conversion to Catholicism, making the analysis of his use of Satanism a key element in understanding his religious transformation and a way to better grasp certain spiritual movements of his time.